Building the data-driven organization - Page, Bob.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) (Santa Clara, CA : O'Reilly, 2011)
"There's never just one way to do things, but for big bets like Big Data, it helps to learn about paths that others have taken. In this presentation, Bob Page, VP Data & Analytics Platforms for eBay, gives a 'behind the scenes' look at the systems and procedures that power decision-making at the world's largest online marketplace."--Resource description page.
Title and publication information from title screen (viewed July 27, 2011).
"Executive summit"--Title screen.
Presenter, Bob Page.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, CA.
Keywords: Data mining; eBay (Firm) -- Data processing; Data marts; Virtual storage (Computer science); Computer storage devices; Electronic books